Las políticas de ayuda y de evacuación de los refugiados españoles en Francia durante la ocupación nazi - Ángel Herrerín López (Cahiers de Civilisation Espagnole Contemporaine)
After the end of the Spanish Civil War, thousands of people took the way of exile. The hard conditions imposed by French authorities to these refugees got worse with the Nazi occupation of France during World War II. Spanish organizations such as the Servicio de Evacuación de Refugiados Españoles (SERE) and the Junta de Auxilio a los Republicanos Españoles (JARE) took care of them. This essay analyses the distribution of aid and the sending of refugees to America by both organizations, with special attention to the JARE, not forgetting questions that affected their work, as the extradition requests by the Franco regime and the policy of accepting refugees by the American countries.